Encounters: American Poets on Paul Celan - various authors (Studies in 20th & 21st Century Literature, 1983)
The Poetry of Exile. Paul Auster. Paul Celan: A Memoir and A Poem. Jerome Rothenberg. Paul Celan. Jed Rasula. Paul Celan. Cid Corman. A Note on Paul Celan. Clayton Eshleman. [Paul Celan.] Jack Hirschman. The Name Reversed — To Paul Anczel. David Meltzer.
Keywords: Paul Celan; poetry; poem; poetics